OP0029 Evaluation of the efficiency of sacroiliac joints corticoid injections under scan control and its relationship with the presence or absence of sacroiliitis lesions seen on mri of patients with spondyloarthritis. (15th June 2017) - Devauchelle, AM; Vittecoq, O; Lequerre, T; Michelin, P; Vincent, F
Abstract : Background: Sacroiliitis is a common symptom for patients suffering from axial and/or peripheral spondyloarthritis. Several studies have demonstrated that long standing corticosteroid injections of the sacroiliac joints can reduce significantly sacroiliitis pain. However, it is difficult to identify predictive factors of good response to the infiltration. Objectives: Hence, our purposes were to evaluate the benefit from sacroiliac long standing corticosteroid injections and to determine if MRI sacroiliac images could predict infiltration's response. Methods: This monocentric study was conducted in real-life circumstances between January 2013 and June 2016 from a standardized procedure. Thirty-one patients having inflammatory pain originating from the sacroiliac joints were infiltrated with a long acting corticosteroid (cortivazol) under CT scan guidance. Hence, 56 sacroiliac joints were injected. To be included, patients had to suffer mainly from low back and/or buttock region in the context of axial or peripheral spondyloarthritis defined by the 2009 ASAS criteria. A contrast enhanced MRI was performed if the last MRI dated more than six months before the infiltration. The main clinical outcome was a global benefit expressed by the patient at day 15 after the infiltration (D15), 1 month (M1), 3 months (M3) and 6 months (M6). Results: 44.1% of patients had a global benefit of at least 50% at D15, 63.6% at M1, 48.3% at M3 and 35.7% at M6. Besides, there was a decrease of the spontaneous Visual Analog Scale for pain (VAS) of the sacroiliac joint at D15, M1 and M3. Likewise, there was a decrease of the provoked VAS of the sacroiliac at D15, M1, M3 and M6. The decrease of the spontaneous VAS was at least of 50% for 35.2% of patients at D15, 41.5% at M1, 25.6% at M3 and 33.3% at M6. There was no decrease of the BASDAI, BASFI, ESR, CRP, ASDAS ESR and ASDAS CRP. Moreover, no relationship was found between the efficiency of sacroiliac infiltrations in terms of global benefit as well as of decrease of the VAS of at least 50% and the presence of sacroiliitis images on the MRI. Neither when looking at the different subtypes of sacroiliitis lesions (bone marrow oedema, synovitis, osteitis). Among the non active sacroiliitis structural lesions (erosions, subchondral sclerosis, bone brigdes...), only fatty involution was statistically more present in the group with a global improvement or a VAS of less than 50%. Conclusions: Long acting corticosteroid infiltrations of the sacroiliac joints are useful in patients suffering from inflammatory sacroiliitis pain. However, the majority of sacroiliac joints images found on a concomitant MRI does not predict the treatment response except fatty involution that seems to be associated with a lower response. Likewise, composite indexes/scores as well as parameters of systemic inflammation are not relevant for the patients follow up in that indication. Disclosure of Interest: None declared